Late small bowel obstruction after blunt abdominal trauma. Issue 927 (1st January 2003) - Maharaj, D; Perry, A; Ramdass, M; Naraynsingh, V
Abstract : Blunt abdominal trauma with intraperitoneal injury usually presents acutely. On rare occasions, such patients can present later on with features of small bowel obstruction due to stricture formation. It is thought that such a delayed stricture is due to subclinical bowel perforation, localised gut ischaemia, or injury to the mesenteric vasculature. This case demonstrates the mesenteric vascular injury theory to be the cause of the bowel stricture.